Dietary astaxanthin alleviates black soldier fly oil-induced negative changes of fatty acids content and muscle quality on Oncorhynchus mykiss via mammalian target of rapamycin and AMP-activated protein kinase pathway - Yongkang Chen; Jian Zhong; Xuanqi Chen; Xiaomin Li; Haiqi Pu; Baoyang Chen; Yucai Guo; Anqi Chen; Wenjie Li; Peng Hu; Xinliang Zhu; Wei Zhao; et al. (Animal Nutrition)
This study evaluated the effect of black soldier fly (Hermetia illucens) larvae oil (BO) produced by a novel technique, subcritical butane extraction, on the flesh quality, lipid nutrients and muscle growth of rainbow trout (Oncorhynchus mykiss) fillet, and investigated the alleviating mechanisms of dietary astaxanthin (AST) supplementation. Two hundred and forty fish (215.16 ± 2.30 g) were distributed to three groups with four replicates. Fish were fed three experimental diets for 8 weeks: the control diet (CD diet), total fish oil of the CD diet was replaced with BO to formulate the BO100 diet, and then 1 g/kg AST was supplemented with the BO100 diet to formulate the AST diet. Results showed that the final body weight and the sarcomere length of fillet were significantly increased and the protein phosphorylation levels of mammalian target of rapamycin (mTOR) and p70 S6 kinase were enhanced in the BO100 group compared to the CD group (P < 0.05). However, there was a reduction in the hardness, springiness and chewiness of fillets, with a decrease in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) levels in the fish of the BO100 group (P < 0.05). Supplementation of AST in the BO100 diet mitigated the impairment of springiness and chewiness and further promoted the sarcomere length of fillet (P < 0.05). Furthermore, dietary AST partially restored the EPA and DHA content of fillet by increasing the phosphorylation levels of serine/threonine kinase (AKT) and AMP-activated protein kinase α (AMPKα) (P < 0.05) and activating the gene expression of unsaturated fatty acid synthesis. To conclude, BO produced by subcritical butane extraction can be a readily available oil source for rainbow trout feed that can be used to promote muscle growth in rainbow trout. Further dietary AST supplementation can alleviate BO-induced lipid accumulation, restore DHA levels and improve the flesh quality of rainbow trout fillet.